Answer:
a)[tex]2 + 3 + 5 + 6 = 16[/tex]
b)[tex]8a + b-9[/tex]
c)[tex]8a - 28b + 15c[/tex]
Step-by-step explanation:
We are given the following in the question:
1. Equivalent expression
[tex]2 + 3 + 5 + 6[/tex]
Since all the terms are like terms, we can write,
[tex]2 + 3 + 5 + 6 = 16[/tex]
2. Sum of given expression
[tex](8a - 2b - 4) \text{ and } (3b - 5)\\ (8a - 2b - 4) + (3b -5)\\= 8a -2b -4 + 3b -5\\\text{Collecting the like terms}\\8a + (-2b+3b) + (-4-5)\\= 8a + b-9[/tex]
3. Standard form of the expression
[tex]4(2a) + 7(-4b) + (3 \times c \times 5)\\=(8a) + (-28b) + (15c)\\=8a - 28b + 15c[/tex]
which is the required standard form of the given expression.